Phase II study of avelumab and trastuzumab with FOLFOX chemotherapy in previously untreated HER2-amplified metastatic gastroesophageal adenocarcinoma - Lee, Michael S; Chao, Joseph; Mulcahy, Mary F; Kasi, Pashtoon M; Alistar, Angela T; Mukherjee, Sarbajit; Akce, Mehmet; Moore, Dominic T; McRee, Autumn J; Somasundaram, Ashwin (The oncologist (Dayton, Ohio), 2025)
Abstract Background Trastuzumab and multiagent chemotherapy have been the standard of care for the 20-30% of metastatic gastric and esophageal adenocarcinomas that overexpress HER2. Preclinical data show that trastuzumab requires a functional adaptive immune system for efficacy, suggesting synergy of trastuzumab combined with immune checkpoint inhibitors, further supported by current clinical studies. Methods HCRN GI17-319 was a multicenter, single-arm, phase II clinical trial with a prespecified 6-subject safety run-in of the anti-PD-L1 antibody avelumab, combined with trastuzumab and mFOLFOX6, in previously untreated, metastatic, HER2-amplified gastric and esophageal adenocarcinomas. The primary endpoint was the best overall response within 24 weeks. Subjects received 9 cycles of induction avelumab, trastuzumab, and mFOLFOX6, followed by maintenance avelumab + trastuzumab. The study was initially designed as a Simon’s 2-stage trial, but enrollment was stopped after the 18-subject first stage for reasons unrelated to safety or efficacy. Results A total of 18 subjects, including the 6-subject safety run-in, were enrolled 4/2019-8/2020. The 24-week response rate was 11/18 (61%; 95% CI: 39%-84%), and the confirmed overall response rate is 9/18 (50%). With a median follow-up of 14.6 months, the median PFS was 8.0 months (95% CI: 5.3-NA) and median OS was 13.1 months (95% CI: 11.5-NA). The regimen was well tolerated, without any new safety signals. Conclusions The combination of avelumab, trastuzumab, and FOLFOX chemotherapy demonstrated some activity, with a reasonable response rate and median PFS. These outcomes provide some support to other clinical trials of similar agents and support the future evaluation of adding avelumab in this setting. NCT03783936.